CD44 promotes hepatocellular carcinoma progression via upregulation of YAP - Jun Zhang (BMC, 2021)
Abstract Hepatocellular carcinoma (HCC) is a common malignancy in human. CD44 is a transmembrane glycoprotein which is frequently overexpressed in cancer of various origins. The function and mechanism of CD44 in HCC remains elusive. In this study, we reported that CD44 was overexpressed in HCC to promote the proliferation and migration of HCC cells via oncogenic YAP, which is the key downstream regulator in Hippo pathway. These findings suggest that CD44-YAP is a probable important axis in pathogenesis of HCC, providing an insight in to HCC pathogenesis as well as potential targets for the intervention of HCC.